Peran E-satisfaction Sebagai Variabel Intervening Dalam Pengaruh E-tailq Terhadap E-loyalty: Studi Pada Pengguna Aplikasi Pegadaian Digital Service Di Kota Bandung - Rustana, Anisa Putri; Hendayani, Ratih (eProceedings of Management, 2024)
In this study, e-satisfaction and e-loyalty of Pawnshop Digital Service Application users in Bandung City arestudied in relation to electronic retail quality (e-tailQ). With causal descriptive data analysis, quantitativeresearch methodology was applied. A total of 198 people were selected as the research sample using a nonprobability sampling approach. Data was collected through the distribution of a Google Form survey, and validity,reliability, and normality tests were conducted using SPSS version 23 software for analysis. The analysisconducted using SmartPLS software version 3.2.9 produced data indicating that e-loyalty is positively influencedby website design, customer service and support, but not by reliability, privacy and security. Furthermore, esatisfaction is strongly positively influenced by website design, customer service and support, privacy and security,but not by reliability. Furthermore, although it does not moderate the relationship between e-tailq and e-loyalty,e-satisfaction has a favorable impact on e-loyalty. Based on these findings, it is recommended that PegadaianDigital Service improve responsive customer service, as well as provide website displays that present efficientinteractive features to ensure user satisfaction and their loyalty. Keyword-e-loyalty, e-satisfaction, E-TailQ, pegadaian digital service.